2016
DOI: 10.1002/jcu.22332
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of myocardial function of patients in the early stage of acute ischemic stroke by two‐dimensional speckle tracking echocardiography

Abstract: GLS and global longitudinal systolic strain rate showed significant improvement together with NIHSS score. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44:305-311, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…Global longitudinal strain is known to be diminished in the acute phase of ischemic stroke, although recovering markedly within 10 days, a time much shorter than the delay from stroke onset to investigational echocardiography in our study 15 . Furthermore, the same study found diminished GLSR in the acute phase, which is not the case for our patients compared with controls.…”
Section: Discussioncontrasting
confidence: 73%
“…Global longitudinal strain is known to be diminished in the acute phase of ischemic stroke, although recovering markedly within 10 days, a time much shorter than the delay from stroke onset to investigational echocardiography in our study 15 . Furthermore, the same study found diminished GLSR in the acute phase, which is not the case for our patients compared with controls.…”
Section: Discussioncontrasting
confidence: 73%
“…All patients underwent comprehensive transthoracic echocardiography examinations, which were conducted according to the guidelines of the American Society of Echocardiography. An ultrasound system (Philips EPIQ 7C, Philips Healthcare, Andover, MA, USA) equipped with a multifrequency transducer (3)(4)(5)(6)(7)(8) and tissue harmonic imaging capability was used. Single-lead electrocardiogram was continuously recorded.…”
Section: Two-dimensional Echocardiographymentioning
confidence: 99%
“…However, there is no significant obstruction of the coronary arteries in patients with NSC. Acute heart failure due to NSC is an important cause of lethal ventricular arrhythmias and mortality 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no significant obstruction of the coronary arteries in patients with NSC. Acute systolic heart failure due to NSC is an important cause of lethal ventricular arrhythmias and mortality 4 .…”
Section: Introductionmentioning
confidence: 99%